Effects of Mergers and Acquisitions on Shareholders’ Wealth of Listed Companies in Kenya - Kioko, Samson Muange (My University, 2018)
This research project sought to establish the effect of Mergers and Acquisitions (M&As) on the shareholders’ wealth of Kenyan listed firms involved in Mergers and Acquisitions. The study adopted a descriptive research design in order to establish the relationship between Mergers and Acquisitions and shareholders’ wealth. The objectives of the study were, to determine how capital base, cost efficiency and market share affect shareholders’ wealth of Kenyan listed companies involved in M&A. Comparisons were made between the mean of 3 years pre-merger/acquisition and 3 years post merger/acquisition financial ratio while the year of merging and period of acquisition were exempted. The study found that the performance of the Kenyan companies in shareholders wealth was on average the same following the M&A. In addition, performance in capital base, cost efficiency and market share was on average the same before and after M&A. Furthermore, the study established that an increase in capital base will lead to a significant increase in shareholders’ wealth, but an increase in either market share or cost efficiency will lead to a decrease in Earnings Per Share (EPS), though not large enough to guarantee a significant change in the shareholders’ wealth. The study recommends the following:- management ought to ensure that earning per share for the shareholders is increased following growth in equity or after an expansion in capital base. In addition, management should not increase the earning per share based on the increase in operating expenses or even after a decrease in operating revenues or following the increase in the cost efficiency. Management ought not to increase the earning per share even after an increase in company’s sales in relation to total sales of the industry. The study recommends that a comparative analysis ought be conducted to ascertain the effect of Mergers and Acquisitions in the different sectors of the economy.